Effect Leading by Example and Coordinaton on Employee Performace - Sudung Simatupang; Marto Silalahi; Pawer Darasa Panjaitan; Hendrick Sasimtan Putra (Cita Konsultindo Research Center, 2024)
A successful organization will be increasingly able to develop and be able to achieve its goals when the leaders in the organization are able to set the right example to achieve employee performance and are supported by the coordination ability of each employee. The results showed that the research variables showed that the leading by example and coordination variables and employee performance had valid criteria, as well as for data reliability testing, that leading by example and coordination and employee performance were reliable criteria. For the results of the regression equation Y = 12,650 + 0,610X1 + 0,993X2, there is a positive direction coefficient of leading by example and coordination on employee performance. The hypothesized results found that leading by example and coordination have a positive and significant effect on employee performance. Leading by example and being able to encourage coordination by creating positive and collaborative relationships that improve employee satisfaction, engagement and performance. These factors contribute to overall organizational success and effectiveness by promoting a culture of accountability, motivation, and effective teamwork.